Factors associated with nephrolithiasis at Royal Prima General Hospital - Suryamin, Ricky; Pulungan, Ica Yulianti (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
The high incidence of kidney stones, or nephrolithiasis, at Royal Prima General Hospital in Medan, affecting 234 patients, constitutes a significant problem requiring resolution. The varied nature of nephrolithiasis presentations observed is attributable to numerous influencing factors. Potential causes of kidney stones include inadequate fluid intake, excessive or insufficient physical activity, obesity, high salt consumption, and other unhealthy behaviours. Furthermore, underlying medical conditions such as diabetes, obesity, and hypertension can elevate the risk of kidney stone formation. This research aimed to analyse the factors associated with nephrolithiasis at Royal Prima General Hospital in Medan. This study employed an observational analytical design with a retrospective approach. The study population comprised the medical records of 234 patients diagnosed with nephrolithiasis who sought treatment at Royal Prima General Hospital in Medan between August 2023 and August 2024. Total sampling was utilised, resulting in a sample size of 234. Data analysis involved univariate, bivariate, and multivariate methods. The results revealed that the majority of patients were aged 46-60 years (n=99, 42.3%) and were male (n=147, 62.8%). Significant associations were found between blood pressure, body mass index (BMI), age, and nephrolithiasis at Royal Prima General Hospital in Medan. However, no significant association was observed between gender and nephrolithiasis. Age (X4) was identified as the variable most strongly associated with nephrolithiasis at Royal Prima General Hospital in Medan.